Galician neomessianism - Gawor, Leszek (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
The article presents the idea of neomessianism, created in the circles of Polish intelligentsia at the end of the 19th century in Galicia – a part of the Polish territory that was subsequently annexed by the Austro-Hungarian Empire. Galician neomessianism referred to the messianic philosophy of Polish Romantics: A. Mickiewicz, J. Słowacki, J.M. Hoene-Wroński and A. Cieszkowski, simultaneously transforming the themes of Romantic messianism, adapting them to the sociopolitical realities of Poland enslaved until 1918 and rebuilt in the interwar period. The article discusses the views of S. Buszczyński, S. Szczepanowski, W. Dzieduszycki, K. Odrzywolski, A. Boleski, A. Gorski, A. Chołoniewski, W. Lutosławski and J. Braun. It also includes reflections on the specificity of Galician neomessianism and its difference in comparison with Romantic messianism.

Artykuł prezentuje ideę neomesjanimu powstałą w środowisku polskiej inteligencji w końcu XIX w. w Galicji – części ziem polskich znajdujących się wtedy pod zaborem c.k. Austro- Węgier. Neomesjanizm galicyjski nawiązywał do filozofii mesjanistycznej polskich romantykow: A. Mickiewicza, J. Słowackiego J.M. Hoene-Wrońskiego i A. Cieszkowskiego. Jednocześnie przetwarzał wątki romantycznego mesjanizmu, dostosowując je do realiow społecznopolitycznych Polski zniewolonej do 1918 r. i odbudowującej się w okresie międzywojennym. W artykule omowiono poglądy S. Buszczyńskiego, S. Szczepanowskiego, W. Dzieduszyckiego, K. Odrzywolskiego, A. Boleskiego, A. Gorskiego, A. Chołoniewskiego, W. Lutosławskiego i J. Brauna. Są tu także zawarte rozważania nad specyfiką galicyjskiego neomesjanizmu i jego odmiennością w porownaniu z romantycznym mesjanizmem.
Keywords: messianism; Galician neomessianism; romanticism; modernism; Polish philosophy; mesjanizm; neomesjanizm galicyjski; romantyzm; modernizm; filozofia polska